Perception management in the United States from the great war to the great crash - Tracy, Jared M. (Kansas State University, 2011)
This study argues that after World War I, corporate executives continued a strategy of perception management (PM) to control Americans’ choices in the commercial sphere and to shape the economic and cultural landscape of the 1920s. The state used PM on an unprecedented scale in 1917 and 1918 to promote a model of loyal American behavior (as part its effort to manage the mobilized U.S. society), but the use of PM did not end after the Armistice. While many historians have seen wartime propaganda measures as the result of special fears and circumstances tied to a sense of pervasive national emergency, they fail to explain the continuation of comparable methods into the period of peace supposedly characterized by a return to "normalcy." Whereas most historical studies sharply delineate between political propaganda and commercial advertising, this study stresses leaders' continuous use of PM to promote their notions of what constituted typical, normal, even loyal American behavior in times of both war and peace. While not a contemporary term in the early twentieth century, PM offers an appropriate conceptual framework to analyze a deliberate strategy at that time. This study defines it as actions used to convey or deny selected information to audiences to influence their emotions, motives, and objective reasoning, resulting in behaviors and actions favorable to the originators’ objectives. During WWI, policymakers and bureaucrats concealed the state's effort to control people's behavior with claims of defending liberty and democracy. After the war, corporate executives used PM to manufacture consumer demand and encourage Americans to think of themselves foremost as consumers. A cross section of political, economic, and cultural history, Perception Management in the United States from the Great War to the Great Crash offers an original perspective that emphasizes the consistency between the wartime and postwar eras by highlighting leaders' ongoing use of perception management to control Americans' behavior.
Keywords: Perception management (PM); Propaganda; Advertising; Marketing; World War I; Public relations; History (0578); Mass Communications (0708); Social Psychology (0451)